Effects of two cryoprotective agents used in slow or rapid standar freeze-thaw procedure on the in vivo survival of morulae from three rabbit strains - Vicente, J.S.=700 1 Garcia-Ximenez, F.
(Es, En)
ilus., 34 ref.
Keywords: CONGELACION; EMBRIONES ANIMALES; LINEAS PURAS; ESPAÑA; DIMETIL-SULFOXIDO 1-2 PROPANADIOL; LINEAS DE CONEJO